Antiosteoporotic activity of Du–Zhong–Wan water extract in ovariectomized rats. (1st September 2016) - Li, Fei; Yang, Xiaolin; Bi, Jianping; Yang, Zhonglin; Zhang, Chunfeng
Abstract: Context Eucommiae Cortex and Radix Dipsaci, occurring in a ratio of 1:1 in Du-Zhong-Wan (DZW), a Chinese herbal medicine, is available as a water extract followed by ethanol precipitation for the treatment of osteoporosis, fractures and menopausal syndrome. Objective This study investigates the protective effects of DZW in ovariectomy (OVX)-induced bone loss in a rat osteopenia model. Materials and methods Sixty Sprague–Dawley rats were randomly divided into the sham-operated group (SHAM) and five OVX subgroups: OVX with vehicle (OVX), 17β-estradiol (E2) and with three graded doses of DZW. Daily oral administration of the different samples started on the fifth week and lasted for 12 weeks, respectively. The body weight, uterus wet weight, serum biochemical parameters, bone mineral density (BMD), bone biomechanical properties, bone microarchitecture and immunohistochemistry were examined. Results Compared with the SHAM group, the DZW treatment significantly reversed the osteoporotic changes in OVX rats. The DZW-H group showed that serum tartrate-resistant acid phosphatase 5b (TRACP-5b) levels reduced by 152.25% ( p  < 0.01) and osteocalein (OCN) levels dose dependently increased by 118.43% ( p  < 0.01) as compared with the OVX group. Compared with the OVX group, the DZW at different three dosages of DZW evidently increased the right femur BMD by 112.43, 114.56 and 116.45%, and dramatically promoted bone quality and bone strength ( p  < 0.05). Further, immunohistochemical evaluation also showed that DZW administration increased ER expression in uteri ( p  < 0.01). Conclusions DZW exhibits an anti-osteoporotic effect, probably mediated via phyto-estrogenic effects. It might be a potential herbal alternative for the management of postmenopausal osteoporosis.